Thermodynamic Study of Reaction of Formation of Cd2 + Cation Complex and 18-Crown-6 Ligand in Two-Component Mixtures of Methanol / Ethyl Acetate, Acetonitrile / Ethyl Acetate, Tetrahydrofuran / Acetonitrile, Methanol / Dimethyl Formamide, Acetonitrile / Methanol And Dimethyl Sulfoxide / Acetonitrile Using Conductometry Method - Ali Mohebi (Journal of Global Pharma Technology, 2018)
The reaction of formation of complex between Cd2 + cation and large ring ligand of 18-crown-6 in solvent systems of methanol / ethyl acetate, methanol / dimethyl formamide, methanol / acetonitrile, acetonitrile / ethyl acetate, acetonitrile / tetrahydrofuran, and acetonitrile / dimethyl sulfoxide was studied at different temperatures by conductometry method. The obtained results indicate that the formed complexes have a stoichiometry of 1: 1 [ML]. The values of the complex stability constants, determined by using conductometry data, show that the formed complex stability is affected by the nature and composition of the solvent. In all two-component mixtures of solvents, a nonlinear relationship is observed for variations in stability constant of the complex, formed by the composition of the solvent. This type of behavior is attributed to solvent-solvent interactions in solvent binary mixtures. The values of the thermodynamic parameters (ΔH ° c, ΔS ° c, ΔG ° c) for the complex have been obtained from temperature dependency of the stability constants. These results showed that the reaction thermodynamics of the formation of the complex is affected by the nature and composition of the mixture of solvents. In the studied solvent systems, entropy or enthalpy, and in some cases, both factors were favorable for complex formation.Keywords: Thermodynamics, 18-Crown-6, CD2 + Cation, Non- Aqueous Two-Component Mixture Solvent, Conductometry.